Late Menstruation Education for Young Women Who Experience Anxiety at MTS Darussalam Blitar - Didit Damayanti; Efa Nuraini; Ayuni Syeifina (MBUnivPress, 2022)
Menstruation is a sign of sexual maturity in young women. Late menstruation is influenced by several factors, namely overweight, nutritional deficiencies, diseases related to reproduction, the influence of smoking, psychosocial factors, genetic disorders, strenuous exercise, anxiety, stress levels of activities and consumption of certain drugs. The purpose of this study was to determine the effect of late menstruation education on adolescent girls with anxiety at MTS Darussalam Blitar. This type of research is pre-experimental with one group pre-test – post-test design. The population of this study was 40 respondents by using purposive sampling technique to get a sample of 36 respondents. The statistical test used is the Wilcoxon test. The results of the statistical test showed that most (75%) of 27 respondents had severe anxiety before the intervention and almost entirely (97.2%) of 35 respondents did not experience anxiety after the intervention. The Wilcoxon test results obtained p value 0.000, which means that there is a significant effect on providing late menstruation education to adolescent girls who experience anxiety. Late menstruation education can help adolescents increase their level of knowledge about menstrual health, and can reduce female adolescent anxiety levels regarding reproductive cycle health. It is suggested that young women can increase their knowledge about reproductive health so as to prevent further anxiety.